PENGARUH CITRA DESTINASI TERHADAP LOYALITAS PENGUNJUNG DI OWABONG MELALUI KEPUASAN SEBAGAI VARIABEL MEDIASI - Oryz Agnu Dian Wulandari; Siti Barokah; Anisa Nur Andina (Universitas Putera Batam, 2019)
Nation's economic growth is currently increasing along with the development of the tourism industry in Indonesia. The increase also affects regional income that has potential tourism objects. This research was conducted in Owabong (Bojongsari Water Tourism Object) with the aim of wanting to find out the influence of destination images on loyalty through satisfaction as a mediating variable. Data obtained by questionnaire method against 145 visitors of Bojongsari water attractions. The method used is quantitative descriptive. The results of this study are destination image and satisfaction have a positive influence on visitor loyalty, but satisfaction is not able to be a mediating variable between destination image and loyalty. Keywords: Destination image, satisfaction, loyalty.